2003
DOI: 10.1038/sj.ijo.0802316
|View full text |Cite
|
Sign up to set email alerts
|

The influence of birthweight and intrauterine environment on adiposity and fat distribution in later life

Abstract: OBJECTIVE:To review the literature on the association between birthweight and body mass index (BMI) and obesity in later life. METHODS: Included in the review were papers appearing in Medline since 1966 and identified using the search terms obesity, body fat, waist, body constitution, birthweight and birth weight. Further papers were identified by examining bibliographies. RESULTS: There is good evidence that there is an association between birthweight and subsequent BMI and overweight in young adults and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
237
2
13

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(263 citation statements)
references
References 83 publications
(70 reference statements)
9
237
2
13
Order By: Relevance
“…[14][15][16][17] Not only lean and fat compartments of body mass but also fat distribution seem to be determined during fetal life. [18][19][20][21][22] However, there are conflicting reports on whether poor fetal growth truly predicts abdominal obesity or whether higher waist-hip ratio is primarily related to a reduced hip size in individuals with low birth weight. 19,21 Another concern in studies reporting the role of birth weight in adult body composition is that assessment of body tissues by anthropometric measurements may introduce inaccuracy.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Not only lean and fat compartments of body mass but also fat distribution seem to be determined during fetal life. [18][19][20][21][22] However, there are conflicting reports on whether poor fetal growth truly predicts abdominal obesity or whether higher waist-hip ratio is primarily related to a reduced hip size in individuals with low birth weight. 19,21 Another concern in studies reporting the role of birth weight in adult body composition is that assessment of body tissues by anthropometric measurements may introduce inaccuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Birthweight has also been reported to affect weight trends in children and adolescents, suggesting that some programming of weight status occurs in utero [5][6][7][8]. Factors that affect birthweight within demographically similar births include pre-pregnancy weight, weight gain during pregnancy, maternal smoking, parity and disease [9].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between birth weight and later obesity has been less studied and there is insufficient evidence. However, available studies suggest rather that high birth weight and rapid weight gain at an early age are favourable conditions to develop obesity in the future (18)(19)(20)(21)(22) . In a Danish population-based cohort study of 252 961 newborns, Rugholm et al showed that the risk of overweight increased consistently with each increase in birth weight category for children aged 6 to 13 years (21) .…”
mentioning
confidence: 99%